Poly(lactic acid) toughen by aromatic sulfonamide toward balanced rheology processing and mechanical properties. (1st June 2022) - Chu, Wenpeng; Yan, Song; Cai, Ziqing; Yang, Shiwen; Hu, Xinghui; Yin, Xianze
Abstract: The inherent brittleness of poly(lactic acid) (PLA) usually limits its application in the high ductile requirements sector. To address the above issue, n-ethyl-p-toluenesulfonamide (N-PTSA) as the toughening agent, was utilized to optimize the rheological and mechanical performance of the PLA matrix. The microstructure, thermal stability, rheological behavior, and mechanical properties of PLA/N-PTSA were systematically investigated. A rheological test showed that N-PTSA can reduce the melt processing viscosity of PLA matrix and the decreasing of processing viscosity strongly depended on the N-PTSA content rather than shear rate. Mechanical properties results confirmed that the 14.7% N-PTSA can improve the toughness of PLA/N-PTSA without deteriorating the tensile strength and Yong's modulus. This reason was ascribed to the reduction of hydrogen bonds of PLA matrix caused by N-PTSA to accelerate the movement of PLA molecular chain meanwhile forming new hydrogen bond between PLA and N-PTSA. By adding N-PTSA, the thermal stability of PLA was decreased. With the synergistic effect of plasticizing and toughening N-PTSA, the rheology and mechanical properties of PLA had been effectively improved.